Controlling Legal Risk for Effective Hospital Management - Park, Hyun Jun (World J Mens Health, 2016)
PURPOSE: To analyze the types of medical malpractice, medical errors, and medical disputes in a university hospital for the proposal of countermeasures that maximize the efficiency of hospital management, medical departments, and healthcare providers. MATERIALS AND METHODS: This study retrospectively reviewed and analyzed 55 closed civil lawsuits among 64 medical lawsuit cases carried out in Pusan National University Hospital from January 2000 to April 2013 using medical records, petitions, briefs, and data from the Medical Dispute Mediation Committee. RESULTS: Of 55 civil lawsuits, men were the main plaintiffs in 31 cases (56.4%). The average period from medical malpractice to malpractice proceeding was 16.5 months (range, 1 month to 6.4 years), and the average period from malpractice proceeding to the disposition of a lawsuit was 21.7 months (range, 1 month to 4 years and 11 months). CONCLUSIONS: Hospitals can effectively manage their legal risks by implementing a systematic medical system, eliminating risk factors in administrative service, educating all hospital employees on preventative strategies, and improving customer service. Furthermore, efforts should be made to establish standard coping strategies to manage medical disputes and malpractice lawsuits, operate alternative dispute resolution methods including the Medical Dispute Mediation Committee, create a compliance support center, deploy a specialized workforce including improved legal services for employees, and specialize the management-level tasks of the hospital.